Myeloidcells in the immunosuppressive microenvironment in glioblastoma: The characteristics and therapeutic strategies - Huang, Boyuan; Zhang, Jin; Zong, Wenjing; Chen, Sisi; Zong, Zhitao; Zeng, Xiaojun; Zhang, Hongbo (Frontiers in Immunology, 2023)
Glioblastoma is the most common and lethal malignant tumor of central nervous system in adults. Conventional therapies, including surgery, radiotherapy, and chemotherapy, has limited success in ameliorating patient survival outcome. The immunosuppressive tumor microenvironment, which is infiltrated with a variety of myeloid cells, has been considered as a crucial obstacle to current treatment. Recently, immunotherapy which has achieved great success in haematological malignancies and some solid cancers, has gradually drawn extensive attentions in treating GBM. In this review, we will present evidences on the features and functions of different populations of myeloid cells, and current clinical advances on immunotherapies for glioblastoma.